ANALISIS PEMAKAIAN IMPLIKATUR PADA KOLOM TAJUK RENCANA SURAT KABAR SUARA MERDEKA EDISI FEBRUARI 2014 - ROSYIDI, MUHAMMAD JUNATUL ATQIYA AL (2016)
Muhammad Junatul Atqiya Al Rosyidi/A 310100199. THE ANALYSIS OF IMPLICATURE USING IN EDITORIAL COLUMN OF SUARA MERDEKA NEWSPAPER 2014 EDITION. Research Paper. School of Teacher Training and Education, Muhammadiyah University Of Surakarta. December, 2015 This study focused on a branch of linguistics, which is pragmatic, especially in the print media newspaper Suara Merdeka. Editorial column becomes the object of study because of the language used by the crew of the Independent Voice media sometimes have a hidden intention. Some intent contained in the editorial column of the newspaper Suara Merdeka worth exploring because of the message, or meaning still can not be expressly understood by the reader. The purpose of this study is two, identifying the form of implicature and identify usage intent Editorial implicature column newspaper Suara Merdeka February issue of 2014. The research is a qualitative descriptive. Data collection techniques were used that technique refer to note. The results of the 52 data analyzed, it can be concluded into two. First, the form of implicature on the editorial column by type of expressive speech act is obtained 9 data, the data 12 declarative speech act, speech act 24 representative of data, speech acts directive 5 data, and speech acts commissive 2 data. Second, the purpose of the use of implicature on the Editorial obtained two purposes, namely direct speech act mean number of 32 data and indirect speech act number 20 of data.